Testing for stochastic dominance up to a common relative poverty line - Tahsin Mehdi (Econometrics, 2020)
Although a wide array of stochastic dominance tests exist for poverty measurement and identification, they assume the income distributions have independent poverty lines or a common absolute (fixed) poverty line. We propose a stochastic dominance test for comparing income distributions up to a common relative poverty line (i.e., some fraction of the pooled median). A Monte Carlo study demonstrates its superior performance over existing methods in terms of power. The test is then applied to some Canadian household survey data for illustration.
Keywords: C01; C12; I32; 330; bootstrap inference; common poverty line; pooled quantile; relative poverty line; stochastic dominance